Legal Instruments in the Development of Electromobility in the European Union, with Particular Focus on Planning Acts - Kokocińska, Katarzyna Elżbieta (Review of European and Comparative Law, 2021)
This paper discusses and characterizes actions undertaken for the development of electromobility as part of the incentive policy pursued by the state. In most European countries, development of the electric vehicle market is largely contingent on electromobility policies, but the measures adopted with a view to supporting it do not always yield the expected results. Effectiveness of supporting actions depends on the cooperation of entities which are responsible for development and social-economic cohesion. The situation requires a multi-level approach to the implementation of electromobility development policy, consolidation of actions of various stakeholder groups, and one common direction in the national development of the electric vehicle market. Development planning acts are the very instruments which serve to enhance the efficacy of efforts undertaken jointly by public administration bodies and foster partnership-based relations between state, regional, and local authorities and their social and economic partners.